Analysis of the implementation results of the didactic model of the cognitive independence formation of non-linguistic specialties students studying foreign languages (Pedagogy of Higher and Secondary Education, 2013)
Dovganets V. I. Analysis of the implementation results of the didactic model of the cognitive independence formation of non-linguistic specialties students studying foreign languages.The article presents the ways of realization of the didactic model of the cognitive independence formation of students of non-linguistic specialties studying foreign languages. The author analyses the implementation results of the didactic model obtained through an empirical study of the object and represents a qualitative-quantitative dynamics of students’ cognitive independence formation on the selected criteria.
Keywords: didactic model; cognitive independence; the study of foreign languages; ways of implementation; results of implementation